2018
DOI: 10.3844/ajptsp.2018.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Taxifolin Potently Diminishes Levels of Reactive Oxygen Species in Living Cells Possibly by Scavenging Peroxyl Radicals

Abstract: Taxifolin, a naturally occurring dihydroflavonol, has been reported to possess antioxidant activity, whereas there is little information regarding its antioxidant potency as a flavonoid. In the present study, the antioxidant efficacy of taxifolin in living cells was compared to that of catechin, a potent radical scavenger, by using flow cytometry with the redox-sensitive fluorescent dye, 2′,7′-dichlorodihydrofluorescein diacetate. Further, diminishing efficacy of taxifolin on peroxyl radicals was assessed by u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…We briefly summarize the examples of the biological effects of (−)-epicatechin as well as (+)taxifolin and/or (−)-taxifolin that were found in the experimental models and that may be relevant for the treatment of hypertension and viral infection through improvements of peripheral vascular function and anti-inflammatory activity as shown in Bernatova and Liskova's paper [105], and references of peripheral vascular function, cardioprotective-and anti-inflammatory effects were summarized in Table 8 [105,. References of cellular and molecular mechanisms underlying the biological effects of epicatechin and taxifolin are listed in Table 9 [105,113,117,121,126,128,[138][139][140][141][142][143][144][145][146][147][148][149][150], and these two flavonoids are effective in ROS (reactive oxygen species) reduction, antioxidant enzymes activation, endothelial NO elevation, and NF-kB reduction.…”
Section: < Biological Effects Of Epicatechin and Taxifolin [105] = 20...mentioning
confidence: 99%
“…We briefly summarize the examples of the biological effects of (−)-epicatechin as well as (+)taxifolin and/or (−)-taxifolin that were found in the experimental models and that may be relevant for the treatment of hypertension and viral infection through improvements of peripheral vascular function and anti-inflammatory activity as shown in Bernatova and Liskova's paper [105], and references of peripheral vascular function, cardioprotective-and anti-inflammatory effects were summarized in Table 8 [105,. References of cellular and molecular mechanisms underlying the biological effects of epicatechin and taxifolin are listed in Table 9 [105,113,117,121,126,128,[138][139][140][141][142][143][144][145][146][147][148][149][150], and these two flavonoids are effective in ROS (reactive oxygen species) reduction, antioxidant enzymes activation, endothelial NO elevation, and NF-kB reduction.…”
Section: < Biological Effects Of Epicatechin and Taxifolin [105] = 20...mentioning
confidence: 99%
“…Reported effects on peripheral vascular function and cardioprotective- and anti-inflammatory effects are summarized in Table 8 [ 107 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 ]. References to the cellular and molecular mechanisms underlying the biological effects of epicatechin and taxifolin are listed in Table 9 [ 107 , 115 , 119 , 123 , 128 , 130 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 ], including effects on reactive oxygen species (ROS) reduction, activation of anti-oxidant enzymes, endothelial NO elevation, and NF-κB reduction.…”
Section: The Effects Of Dietary Flavonoids On Microvascular Healthmentioning
confidence: 99%
“…Reported effects on peripheral vascular function and cardioprotective-and anti-inflammatory effects are summarized in Table 8 [107,. References to the cellular and molecular mechanisms underlying the biological effects of epicatechin and taxifolin are listed in Table 9 [107,115,119,123,128,130,[140][141][142][143][144][145][146][147][148][149][150][151][152], including effects on reactive oxygen species (ROS) reduction, activation of anti-oxidant enzymes, endothelial NO elevation, and NF-κB reduction. Table 9.…”
Section: Biological Effects Of Epicatechin and Taxifolin [107] = 2021mentioning
confidence: 99%
“…A previous search, using the Connectivity Map developed by the Broad Institute, found that GHK could alleviate impairment of TGFβ1 signaling (Pickart et al, 2017), a pathway associated with Aβ deposition and neurofibrillary tangle formation (Bosco et al, 2013). In addition, GHK has been shown to be an endogenous antioxidant by decreasing hydroxyl and peroxyl radicals (Sakuma et al, 2018), and improve cognitive performance in aging mice (Rosenfeld et al, 2023).…”
Section: Introductionmentioning
confidence: 99%